A workplace health promotion application of the Precede-Proceed model in a regional and remote mining company in Whyalla, South Australia. Issue 3 (14th September 2015) - Post, Dannielle Kay; Daniel, Mark; Misan, Gary; Haren, Matthew T
Abstract : Purpose: – Workplace health promotion enables the dissemination of health-related information to a large portion of society and provides a vehicle for translating results of efficacy studies to effective lifestyle interventions under less controlled real-world conditions. To achieve effectiveness there needs to be a systematic approach to the design, implementation, and evaluation of workplace health promotion interventions. The purpose of this paper is to describe the development of a workplace programme in a mining and steel making town in regional South Australia. Design/methodology/approach: – The Precede-Proceed model (PPM) was used as a framework to design the development, implementation, and evaluation of the programme. Findings: – Quality of life issues and antecedents of modifiable behavioural and environmental factors to be targeted by interventions were identified. Relevant socio-behavioural theories were used to guide intervention development and evaluation. An intervention programme was planned to enable the delivery of educational and skills-development strategies by peers within structured organisational work units. Originality/value: – This research utilises the PPM to develop, implement, and evaluate intervention strategies targeting the development of diabetes and cardiometabolic risk in a remotely located workplace population. Novel to this approach is the utilisation of the entire PPM in the research; the multiple baseline, interrupted time series design of the study; and its application in a workplace environment noted for increased health risk factors, within a community at high risk of development of type 2 diabetes.